STRATEGI PENANGANAN ANAK BERHADAPAN DENGAN HUKUM MELALUI UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Nurul Farida (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2020)
The deviation of the behavior of today's children has crossed the appropriate limit. Many children begin to indulge in casual sex, narcotics, violence, thuggery, and many more actions that can be categorized as unlawful. The Law mandates that children are a gift of God Almighty who has the dignity and dignity as a full human being, and therefore, they are entitled to special protection, especially legal protection in the judicial system by providing special protection to children who face the law. The Indonesian Child Protection Commission (KPAI) stated that the number of children facing the law (ABH) is increasing year on year. Nevertheless, in accordance with UNICEF's mandate, the involvement of children in criminal justice for adults can hurt children, both psychologically and socially. The formulation of the problem in this writing is